The coronavirus conundrum - From pandemic to endemic COVID-19 – Should we continue taking care of ourselves? - Pacheco-Romero, José (2023)
It seems that things are calming down with SARS-Cov-2, as there are no longer dailyreports and notes of findings of new variants and subvariants of the virus, as wellas clinical changes in symptomatology, hospitalizations, severity, and deaths due toCOVID-19. We do not know how we should guard against viral infection during theimpending endemic phase of the disease, knowing the complex health problems ofprolonged COVID if we contract the virus. In this article we describe the latest knowncoronavirus mutations, how they affect certain organs and systems, the advantageof a better response to infection in people with healthy lifestyle, the rebound ofsymptomatology, reinfections at the time of the vaccine, prolonged COVID, excessmortality of physicians who attended the first waves without vaccine, and some newsand knowledge about COVID in the pregnant woman and her fetus and newborn; thefuture of the newborn born to a mother with COVID remains unknown. In the COVIDendemic, should we continue to protect ourselves? How?